Linking CEOs’ Pride to Firm Strategy and Performance - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2011)
We extend achievement attribution theory to examine how, upon perceiving success of their organizations, CEOs experience pride in their own and their firms’ efforts (authentic pride) or pride in capabilities (hubristic pride); and how this matters for their expectations of firm performance. We outline how such forms of pride trigger different kinds of firm outcomes; and we propose that emotional self-regulation processes can shape what kind of pride CEOs experience.